Yoga Anak untuk Meningkatkan Konsentrasi Belajar di TK Sukomarsudi Putro I - Setiyowati; Fatchiyah, Siti; Purwati; Rila Aneka; Sofiyanti, Ida (Universitas Ngudi Waluyo, 2024)
The age of preschool children is the age range of 3-6 years with various characteristics, at this time children like to imagine believing that they have strength. Preschool-age children are in a golden period of human development because at that time their physical and non-physical developments develop rapidly. The golden period is the age of children when they are 0-5 years old, this period is a sensitive and critical period, where children are especially easy to receive stimuli from their environment and is a period of brain development. Thus the golden age lies at an early age, to be able to stimulate the development of children's intelligence so that they can develop optimally to be a shared responsibility between teachers and parents at home. It is quite difficult for a child to be able to sit still for a long time and concentrate. So one of the things that can be done is with children's yoga. Several studies explain that yoga practice can help children to concentrate, regulate their breath, calm their minds with certain poses. This service is carried out in 4 stages, namely observing children's learning in the classroom, licensing to the school, carrying out activities, testimonials from teachers and children. This service aims to increase children's learning concentration and provide education to teachers at schools about children's yoga. The population of this service is kindergarten students, totaling 15 children. This activity uses leaflets and is carried out face-to-face at TK Sukomarsudi Putro I. Abstrak Usia anak prasekolah adalah rentang usia 3-6 tahun dengan berbagai macam ciri, pada masa ini anak-anak senang berimajinasi percaya bahwa mereka memiliki kekuatan. Anak usia prasekolah berada dalam masa emas perkembangan manusia karena pada masa itu perkembangan fisik maupun nonfisik berkembang secara pesat. Masa emas adalah usia anak ketika berumur 0-5 tahun, masa ini merupakan periode sensitif dan kritis, dimana anak secara khusus mudah menerima stimulus-stimulus dari lingkungannya dan merupakan masa perkembangan otak. Dengan demikian masa emas (golden age) terletak pada usia dini, untuk mampu menstimulasi perkembangan kecerdasan anak agar dapat berkembang maksimal menjadi tanggung jawab bersama antara guru dan orang tua dirumah. Agak sulit untuk anak bisa duduk diam di waktu yang lama dan berkonsentrasi. Maka salah satu hal yang dapat dilakukan yaitu dengan yoga anak. Beberapa studi menjelaskan bahwa latihan yoga dapat membantu anak untuk berkonsentrasi, mengatur napas, menenangkan pikiran dengan pose-pose tertentu. Pengabdian ini dilaksanakan dalam 4 tahapan yaitu pengamatan pembelajaran anak di ruang kelas, perizinan kepada pihak sekolah, pelaksanaan kegiatan, testimoni dari guru dan anak. Pengabdian ini bertujuan untuk meningkatkan konsentrasi belajar anak serta memberikan edukasi kepada guru di sekolah tentang yoga anak. Populasi dari pengabdian ini adalah siswa TK yang berjumlah 15 anak. Kegiatan ini menggunakan leaflet dan dilakukan secara tatap muka di TK Sukomarsudi Putro I.